Nafcillin degradation by heterogeneous electro-Fenton process using Fe, Cu and Fe/Cu nanoparticles. (May 2020) - Campos, Sebastian; Salazar, Ricardo; Arancibia-Miranda, Nicolás; Rubio, M.A.; Aranda, Mario; García, Alejandra; Sepúlveda, Pamela; Espinoza, L. Carolina
Abstract: Heterogeneous electro-Fenton (HEF) is as an alternative to the conventional electro-Fenton (EF) process. HEF uses a solid phase catalyst, whereas EF employs a solubilized one. This implies that in HEF, material can be recovered through a simple separation process such as filtration or magnetic separation in HEF. HEF also has the advantage of not requires a previous pH adjustment, which facilitates working in a higher pH range. In this work, Fe, Cu and Fe/Cu bimetallic nanoparticles (Fe/Cu NPs) were synthesized, characterized and used for the degradation of Nafcillin (NAF). The effect of the adsorption and the anodic oxidation (AO-H2 O2 ) process was tested to assess their influence on HEF. NAF adsorption did not exceed 24% of antibiotic removal and the AO-H2 O2 process eliminated the total NAF after 240 min of electrolysis. Through the HEF process, the antibiotic was completely removed using Fe/Cu NPs after 7.0 min of electrolysis, while these NPs, mineralization reached 41% after 240 min. In this case, NAF degradation occurs mainly due to the generation of hydroxyl radicals in the BDD electrode, and the Fenton reaction with Fe and Cu NPs. The main organic intermediates produced during the degradation of NAF by HEF were identified allowing the proposal of degradation pathway. Finally, the antibiotic was also completely eliminated from a wastewater from slaughterhouse after 15 min of treatment by HEF and using Fe/Cu bimetallic NPs. Highlights: Fe/Cu monometallic and bimetallic NPs were synthesized to be used as Fenton catalyst in HEF. Fe/Cu bimetallic NPs allow the antibiotic elimination at very short electrolysis times. New metal oxides were detected after using Fe/Cu bimetallic NPs in the HEF. Fe/Cu bimetallic NPs were successfully recovered and reused in three consecutive cycles.